ANALISIS PENGARUH PENAMBAHAN LIMBAH STYROFOAM PADA ASPAL POROS AC-WC TERHADAP STABILITAS DAN KEPADATAN NR - Rosyad, Farlin; Barokah, Muhammad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads are infrastructure that plays a very important role in the progress of an area which is a link between one region and other regions. In an effort to add fine material substitution materials that can be used as materials in asphalt mixtures, sterosomes that are easily obtained are used in research as an alternative to fine materials in asphalt mixtures. The purpose of this pelnellitian is ulntulk melngarulh from Styrofoam waste telrhadap karaktelristik asphalt by rolling the marshall's pelnguljian. This pelnellitian is rounded by 24 belnda ulji, where the ulji object that rolls added Styrofoam waste as an additional fillelr of 10%, 12%, 14% and 16% each is rounded by 6 belnda ulji. Serve belnda ulji that is not covered with Styrofoam waste and rounded around 3 test objects. While the test belnda that was not given Styrofoam waste was also rounded as many as 3 ulji belnda. The ability to add Styrofoam waste as a fillelr to each ulji belnda is 6% of the total asphalt campulran agrelgat. Conducting telrhadap telrhadap telrikat variable, namely marshall and variable belbas characteristics, namely the addition of Styrofoam Waste as a sulbtitulsi on asphalt (AC-WC). The effect of Styrofoam Waste Prelselntasel as a sulbstitulsi telrhadap Stability and Density, in this case Stability and Density are melted by Marshall Stability The rest of the gap on flelxibility is released by Marshall Qulotielnt, the value of Residual Marshall Stability, in the 10% Styrofoam Waste campulran obtained a value of 91.45%, in the mixture of 12% Styrofoam Waste obtained a value of 92.77%, in a mixture of 14% Styrofoam Waste obtained a value of 93.22%, in the 16% Styrofoam Waste mixture obtained a value of 92.86%, while in Marshall Qulotielnt obtained a value of 356 kg / mm in a mixture of 12% Styrofoam Waste, 371 kg / mm in a mixture of 14% Styrofoam Waste, and 350 kg / mm in a mixture of 16% Styrofoam Waste.Keyword : Sterofoam, Asphalt rubber, AC-WC, Stability, Density